Factors Related To Blood Pressure In Adults In The Intensive Care Unit Bhayangkara Hospital Raden Said Sukanto Year 2019 - Wisnu Wibowo, Agung; Ifadah, Erlin; Jamiatun, Jamiatun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
Abstract Blood pressure is a measure of the force that directs blood to flow through the body's circulation. Blood pressure is needed by the body to carry oxygen and other nutrients to the body's tissues. The purpose of this study was to determine the factors associated with blood pressure in patients in the Intensive Care Unit (ICU). This study uses a quantitative method with an analytic survey approach. The population in this study were all patients in the ICU ward at Bhayangkara Tk.I R. Said Sukanto Hospital, as many as 133 patients. The sample required in this study is 100 respondents. The statistical test used was chi square. There is a relationship between age (p = 0.032), gender (p = 0.016), medication (p = 0.009), and exercise (p = 0.000) with blood pressure in patients in the Intensive Care Unit (ICU) Bhayangkara Hospital Tk.I R . Said Sukanto. There was no relationship between races (p = 0.052). The results showed an association between age, gender, medication and exercise with blood pressure Keywords: Age, Gender, Race, Medication, Exercise, Blood Pressure